Strategic Planning of Instagram Social Media for the Promotion of Mahakam Seafood - Kurniawan, Nadya Josephine; Teguh, Monika (Indonesian Journal of Social Science Research, 2026)
The rapid expansion of the food and beverage (F&B) industry, particularly in the seafood segment, has intensified competition and heightened the importance of effective digital marketing strategies. This study employs a case study approach to investigate the decline in revenue experienced by Mahakam Seafood, attributed to suboptimal digital marketing implementation and limited human resource capacity. The research aims to develop a structured Instagram marketing strategy to enhance promotional effectiveness and improve sales performance. The strategy design is grounded in the Hierarchy of Effects and Lovemarks frameworks, supported by the application of SMART Goals and the Segmentation, Targeting, and Positioning (STP) model to ensure strategic alignment and measurable outcomes. The research process includes situational analysis, development of content pillars and content planning, creation of visual and communication guidelines, preparation of content mock-ups, and formulation of an implementation and budget plan. The findings provide a systematic and practical social media strategy framework that can improve the consistency and effectiveness of Instagram marketing activities, offering managerial implications for small and medium-sized enterprises in the F&B sector.